Tingkat Pemahaman Pelaku Usaha Pasar Rakyat Jambangan Tentang Praktik Pungutan Liar dalam Tindak Pidana - Meilenia, Dinda; Kartika Sari, Maya Mustika (Kajian Moral dan Kewarganegaraan, 2025)
The Jambangan People's Market (PRJ) is a relocation of street vendors who previously sold their goods around the Al-Akbar Mosque area in Surabaya and is managed by the Small and Medium Enterprises and Trade Cooperative Office. This has led to the establishment of new regulations by business actors, namely the exemption of fees for stall facilities, electricity, water, and security. The purpose of this study is to determine the level of understanding among business operators at the Jambangan People's Market in Surabaya regarding illegal fees in criminal acts. This is a quantitative descriptive study using a survey method with data collection techniques involving tests. The research subjects are business operators at the Jambangan People's Market in Surabaya, with a sample size of 196 business operators selected using simple random sampling, based on a 5% margin of error. The research source used a questionnaire consisting of 25 valid test questions with a reliability coefficient of 0.339. The data analysis technique used was quantitative descriptive statistics with percentage calculations. The research results indicate that the level of understanding of business operators at the Jambangan Traditional Market in Surabaya regarding illegal collection practices in criminal acts is overall in the “very good” category, with 106 individuals (54.1%). However, the “very low” category achieved the highest score, with eradication efforts reaching 26%. Thus, this study has a unique finding: high knowledge should trigger effective eradication efforts. However, knowledge alone is insufficient; community participation and integrated policies that support effective results in addressing the issue are also necessary.